A comparison of the energy demands of quadrupedal movement training to walking - Buxton, Jeffrey D.; Sherman, Sally A.; Sterrett, Micah T.; Kannel, Kristia D.; Blanchflower, Morgan E.; Jancay, Kelli T.; Jenkins, Anna K.; Donofrio, Troy P.; Prins, Philip J. (Frontiers in Sports and Active Living, 2022)
BACKGROUNDː Quadrupedal movement training (QMT) is a novel alternative form of exercise recently shown to improve several fitness characteristics including flexibility, movement quality, and dynamic balance. However, the specific energy demands of this style of training remain unknown. Therefore, the purpose of this study was to compare the energy expenditure (EE) of a beginner-level quadrupedal movement training (QMT) class using Animal Flow (AF) to walking, and to compare EE between segments of the AF class and gender. METHODSː Participants (15 male, 15 female) completed 60-minute sessions of AF, treadmill walking at a self-selected intensity (SSIT) and treadmill walking at an intensity that matched the heart rate of the AF session (HRTM). Indirect calorimetry was used to estimate energy expenditure. RESULTSː AF resulted in an EE of 6.7 ± 1.8 kcal/min, 5.4 ± 1.0 METs, and HR of 127.1 ± 16.1 bpm (63.4 ± 8.1% of the subjects’ age-predicted maximum HR), while SSIT resulted in an EE of 5.1 ± 1.0 kcal/min, 4.3 ± 0.7 METs, HR of 99.8 ± 13.5 bpm (49.8 ± 6.7% age-predicted maximum HR), and HRTM resulted in and EE of 7.6 ± 2.2 kcal/min, 6.1 ± 1.0 METs, and HR of 124.9 ± 16.3 bpm (62.3 ± 8.2% age-predicted maximum HR). Overall, EE, METs, HR and respiratory data for AF was greater than SSIT (p’s < 0.001) and either comparable or slightly less than HRTM. The Flow segment showed the highest EE (8.7 ± 2.7 kcal/min), METs (7.0 ± 1.7) and HR (153.2 ± 15.7 bpm). Aside from HR, males demonstrated greater EE, METs, and respiratory values across all sessions and segments of AF than females. CONCLUSIONSː QMT using AF meets the ACSM’s criteria for moderate-intensity physical activity and should be considered a viable alternative to help meet physical activity guidelines.